The Model of the Internal Monitoring Unit After the Determination of IAIN to Become a UIN - Erwin, Erwin; Misneli, Misneli; Nasfi , Nasfi (IJOSMAS, 2022)
The Internal Supervisory Unit (SPI) at State Islamic Religious Universities (PTKIN) carries out supervisory duties in accordance with the Minister of Religion Regulation of the Republic of Indonesia No. 25 of 2017. SPI as one of the supervisory system tools, is required to focus on achieving governance, control, risk management, not just just administrative work. The existence of SPI at PTKIN must be understood by elements within the organization and have the same perception regarding the scope of the audit area by the organization and top management. This study uses the